Association between Participation in a Preclinical Surgery Elective and Future Match into Surgical Residency. Issue 5 (May 2023) - Rudasill, Sarah; Negrete Manriquez, Jose A.; Benharash, Peyman; Kim, Dennis; Yetasook, Amy; Bowens, Nina; de Virgilio, Christian
Background: Since 2013, we have offered a robust "Introduction to Surgery" elective (ITS) for preclinical medical students. The present study investigates whether participants of the ITS elective were more likely to match into surgical residencies than non-ITS participants. Methods: This is a retrospective case-control study of medical students from two medical schools in Southern California who participated in the ITS elective and those who did not. Descriptive results and univariate analysis using STATA were utilized to analyze the de-identified data who matched between 2016 and 2021 were included. Results: Overall, 87 (8.9%) of the 982 matched students participated in the ITS elective, with an increase in participation from 1.2% in 2016 to 13.9% in 2021 ( P < .001). Among ITS participants, 49.4% matched into a surgical specialty compared to only 22.9% for non-ITS students ( P < .001). There was no difference between ITS and non-ITS students with regards to procedural specialty match (14.9% vs 12.6%, P = .537). Conclusion: ITS participants were more than twice as likely to match into a surgical specialty than non-participants. Future qualitative research will help discern the relative impact of the ITS course versus a student's baseline predisposition to surgery.